2008
DOI: 10.1521/jscp.2008.27.10.1165
|View full text |Cite
|
Sign up to set email alerts
|

When is Crying Cathartic? An International Study

Abstract: The idea that crying is a cathartic experience, leading to relief from distress, has deep roots. however, empirical evidence for catharsis after crying is mixed. one explanation for the inconsistent results is that variations in the social context of the crying situation determine whether or not crying-related catharsis occurs. To evaluate the role of social context and other contextual features in crying-related catharsis, self-report data were collected on characteristics of the most recent crying episode an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 27 publications
(41 reference statements)
5
88
2
Order By: Relevance
“…Expert discussion yielded the items using literature on crying and Sjögren's syndrome, existing items from crying inventories (Bylsma et al, 2008;Vingerhoets, 1995;Vingerhoets, Boelhouwer, Van Tilburg, & Van Heck, 2001), and in-depth interviews with patients with primary Sjögren's syndrome. The final version included 21 items to be answered on a 4-point Likert scale, with the response options ''1 = seldom or never,'' ''2 = sometimes,'' ''3 = regularly,'' and ''4 = very often.''…”
Section: Cryingmentioning
confidence: 99%
See 3 more Smart Citations
“…Expert discussion yielded the items using literature on crying and Sjögren's syndrome, existing items from crying inventories (Bylsma et al, 2008;Vingerhoets, 1995;Vingerhoets, Boelhouwer, Van Tilburg, & Van Heck, 2001), and in-depth interviews with patients with primary Sjögren's syndrome. The final version included 21 items to be answered on a 4-point Likert scale, with the response options ''1 = seldom or never,'' ''2 = sometimes,'' ''3 = regularly,'' and ''4 = very often.''…”
Section: Cryingmentioning
confidence: 99%
“…Another study observed that patients with rheumatoid arthritis who were able to cry with tears in an emotional experiment had better disease control than patients who were not able to cry with tears (Ishii, Nagashima, Tanno, Nakajima, & Yoshino, 2003). A reduction of crying ability may be determined by a multitude of factors independent of ocular dryness that may differ between people with and without a chronic disease such as emotional (e.g., depressive mood), cognitive and social context variables (Bylsma et al, 2008;Messmer, 2009;Rottenberg, Bylsma, Wolvin, & Vingerhoets, 2008;Vingerhoets, Van den Berg, Kortekaas, Van Heck, & Croon, 1993;Vingerhoets et al, 2000;Vingerhoets, 2013).…”
Section: Cryabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Because researchers have previously found differences in the rates of TCIT based on clinician's level of experience and theoretical orientation (Blume-Marcovici, et al, 2013), and because of the documented differences in rates of crying between males and females in general (Bylsma, Vingerhoets, & Rottenberg, 2008;Vingerhoets, Cornelius, Van Heck, & Becht, 2000) despite similar rates of TCIT (Blume-Marcovici, et al, 2013), and since the expression of emotion is moderated by culturally determined display rules (Ekman, 1973;Matsumoto, 1989) and freedom of expression in a given culture (van Hemert, van de Vijver, & Vingerhoets, 2011), we also aimed to investigate whether any demographic or clinical experience variables were related to different experiences of training, supervision and consultation with respect to TCIT.…”
mentioning
confidence: 99%